3‐D numerical simulations for polycondensation of poly(p‐phenylene terephthalamide) in twin screw extruder. Issue 11 (19th January 2017) - Zong, Yuan; Tang, Hao; Zhao, Ling
Abstract : Poly(p‐phenylene terephthalamide) (PPTA) is a typical high‐performance fiber and usually synthesized by low temperature solution polycondensation in twin screw extruder. During the reactive extrusion, flow behavior, rheokinetics, and temperature are highly coupled, which makes it difficult to ensure the quality of product. In the present work, the rheokinetics of the PPTA solution is established by experiments and its reactive extrusion is investigated via 3‐D numerical simulation. The flow pattern, molecular weight distribution and temperature have been investigated for the extruders with three different elements, i.e., full flight screw (FF), kneading block (KB), and screw mixing element (SME). The results indicate that the unique flow characteristic of different screw elements affects mixing experience of the reactants and further the PPTA qualities. By numerical simulation, it shows the temperature increase within the tested extrusion stage is 7 K and reaction heat is found the main energy source for extrusion stage. Furthermore, heat removal method is verified with consideration of industrial production process. The numerical simulation work also discusses the reaction and mixing process in the extruders with three combined screws. The results show the introduction of more reverse FF and KB elements can lead to higher quality of PPTA. POLYM. ENG. SCI., 57:1252–1261, 2017. © 2017 Society of Plastics Engineers